A Study on Heavy Metals Contamination in Agricultural Soils: Implications for Food Security and Public Health (Journal of Advances and Scholarly Researches in Allied Education, 2019)
India's capacity to produce enough food to fulfill its population's demands has a major impact on the country's economic progress. Increasing food production was the driving force behind the Green Revolution, which was born out of the necessity to feed a burgeoning population. There is a growing problem with heavy metal poisoning in the environment, and the detrimental effects it is having throughout the world are making people very concerned. Agriculture and metal businesses, together with poor waste management, fertilizers, and pesticides, are polluting our rivers and soils. Heavy metals have also been implicated in a wide spectrum of human ailments. The bioaccumulation, toxicity, and transmission mechanisms of both heavy metals and insecticides, Agriculture soil heavy metal contamination has had significant detrimental effects on human health and the environment. Major attention has thus been focused on the assessment of heavy metals in agricultural land to enhance the environment and ensure the well-being of humans. Food grains have been able to develop and remain viable because to the employment of these agricultural technologies, but they have come at a considerable cost to the environment and human health.